How we did it: the development of a specialist registrar training programme by the Mersey Accident and Emergency Trainees' Association. Issue 5 (September 1997) - Davies, F; Geary, U; Soulsby, T; Good, A
Abstract : Over the last three years the accident and emergency trainees in Merseyside have developed a self directed training programme which now consists of twice monthly meetings. This has been achieved through a process of evolution, shaped by the core curriculum, and supervised by the region's consultants with the support of the postgraduate dean. The meetings have proved both popular and valuable. The development and format of the scheme is presented in the hope of stimulating others to work together to improve the training of specialist registrars.